Early Predictors of Sexually Intimate Behaviors in an Urban Sample of Young Girls - Hipwell, Alison E. (2010)
In recent years, concern has been raised about girls’ involvement in sexual activity at progressively younger ages. Little is known about the prevalence of emerging intimate behaviors, the psychosocial factors associated with these behaviors, or the moderating effects of race on these associations in early adolescence. In the current prospective study, we examine the prevalence and predictors of sexually intimate behaviors at age 12 years in an urban community sample of 1,116 racially diverse girls. Cluster analysis revealed three groups at age 12: none, mild (e.g. holding hands) and moderate (e.g. laying together). Minority group girls reported higher rates of both mild and moderate sexually intimate behaviors compared with European American girls. After controlling for the significant effects of age 11 intimate behaviors, lifetime alcohol use, poor parent-child communication, deviant peer behavior, onset of menarche, and interactions between race and impulsivity, social self-worth and depression uniquely increased the odds of engaging in moderately intimate behaviors at age 12 years. Parenting characteristics increased the likelihood of moderate, relative to mild, behaviors. For European American girls only, high levels of impulsivity and low social self-worth were associated with a higher likelihood of engaging in moderate intimate behaviors, whereas high levels of depressive symptoms reduced the odds. The results suggest that early prevention efforts need to incorporate awareness of different social norms relating to sexual behavior.